Performance analysis of a pilot-scale modified air heated and dual heated humidification-dehumidification desalination system. (25th March 2023) - Jawad, Saad Abdul; Lawal, Dahiru U.; Antar, Mohamed A.; Sharqawy, Mostafa H.; Khalifa, Atia E.; Zubair, Syed M.
Highlights: A pilot scale air humidification–dehumidification system is experimentally investigated. Performances of modified air heated mode and dual heated mode are compared. Different heat rate ratio are investigated, The productivity of the HDH unit reached a maximum of 117.2 kg/day. The system with a heat rate ratio greater than one yields superior performance. Abstract: Humidification-dehumidification (HDH) desalination systems offer an effective decentralized solution to meet the potable water demands of small and medium - size communities. Amongst many HDH configurations, the modified air heated and dual heated HDH cycles have demonstrated promising results in several studies based on small lab-scale setups, where the pilot scale experimental data are lacking in literature. In this study, the performance of both modified air heated and dual heated cycles are experimentally investigated using a new pilot-scale system to benchmark the performance for scaling-up the HDH system. The concept of heat rate ratio is explored practically in a new approach by splitting up the energy supply between water and air streams in the dual heated cycle. Both cycles operate in closed-air open-water cycle. In the modified air heated layout, humid air is heated after the humidifier, whereas in the dual heated mode, both water and air are heated simultaneously before and after the humidifier. The effects of changing the mass flowrate ratio on the performance dynamic indices, including productivity, gained output ratio, product cost, recovery ratio, top system temperature, specific energy consumption, and heat capacity ratio of both configurations are investigated. Results indicate that the dual heated system performs better than the modified air heated cycle, with a maximum freshwater production rate of 117.2 kg/day and 72.7 kg/day for dual the heated and modified air heated cycles, respectively. Dual heated system also recorded peak recovery ratio of 2.24 % while modified air heated cycle attained a highest RR of 1.26 %. Furthermore, the estimated peak gained output ratio for modified air heated and dual heated cycles are 0.53 and 0.74, respectively. The dual heated cycle also recorded the lower freshwater cost of 0.055 $/kg, while the best product cost for the air heated cycle is 0.079 $/kg of freshwater.